Adducing to the Defence of Necessity as Precluding Responsibility of States for Internationally Wrongful Acts in Imamayeh Fiqh and International Law and with a Case Study of Human Shield - Sayyed Ghasem Zamani; Abbas Ali Azimi Shushtari; Mojtaba Afshar (آموزه‌‌های فقه مدني)
“Necessity” as one of the elements of precluding international responsibility of states is interest of states in certain and exceptional circumstances. The comparative study of necessity in two systems of international law and Islam represents some distinctions along with many similarities. The application of this the essential principle in armed conflict titled “military necessity” to violate the safety of the civilians who are shield is a challengeable matter because the human shield has been prohibited and criminalized by international law and Islam. Therefore, the question is what the nature and effects of the principle of necessity are in the international law and Imamayeh fiqh and how the conduct of parties in dispute towards civilians and their properties which have been used as a shield should be. This note with the qualitative research method and with utilization of the legal interpretation methods of the Quran verses and traditions and the opinion of jurists and historical study of the holy prophet biography in wars has been adopted. By reviewing jurisprudential documents and sources it has achieved the result that the principle of necessity has an exceptional nature in both legal systems and merely it is permitted in the case that the essential interests of the state is in danger. Consequently, with the prohibition of any damage to the human shield, in the situation of the exigency of necessity and with observing the cautious measures, it is yet possible to attack military objectives.